Polyhydroxybutyrate (PHB) production and methane uptake by methanotrophic bacteria in a membrane-based reactor - Taskan, Banu; Taskan, Ergin; Lai, YenJung Sean; Eustance, Everett; Mahmood, Maheen; Luo, Yi-hao; Rittmann, Bruce E. (Elsevier Ltd, 2025)
Methanotrophic bacteria use methane (CH4) as an electron donor and carbon source for growth and to produce a variety of valuable byproducts, including polyhydroxybutyrate (PHB), a feedstock for bioplastics. This study evaluated the effects of three independent parameters (nitrogen source, dissolved oxygen (DO) concentration, and CH4 availability) on biomass and PHB yield. The work employed a membrane-based approach to deliver CH4 and O2 gases independently for methanotrophic growth, a process referred to as Membrane Oxygenation and Methanotrophy (MOM). Performance metrics included bacterial yield, CH4 consumption rate, PHB content, and microbial community composition. Ammonium (NH4+) as an N-source with low DO concentration led to the highest biomass yield (up to 0.59 g produced biomass/g CH4) and PHB content (up to of 36% of dry weight). The MOM improved CH4 utilization efficiency up to 95.8% without gas circulation. Limiting CH4 availability during N-depletion promoted the PHB content of the methanotrophic bacteria. However, excess CH4 in the headspace (>70% CH4 not being utilized) for the limited DO condition inhibited biomass growth and PHB production. Shallow metagenomic analysis showed that the bacterial species in the MOM reactors mainly belonged to the genera Methylocytis (up to 87% relative abundance) and Hyphomicrobium (up to 70% relative abundance). Methylocystis, a Type II methanotroph known to produce PHB, became dominant during the conditions that led to the highest PHB content. The findings demonstrate the MOM operated with lower CH4 gas pressure and limited DO promoted CH4 utilization and conversion toward PHB production. © 2025 Elsevier Ltd
Keywords: Gas-transfer membrane; Methane mitigation; Methane-oxidizing bacteria; Microbial community; Polyhydroxybutyrate (PHB) production